2018
DOI: 10.4236/pp.2018.910031
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Aqueous Extract of <i>Schumanniophyton magnificum</i> Harms on Sexual Maturation and Fertility of Immature (K. schum) Female Rat

Abstract: The aim of the study was to bring scientific evidence of the curative action of the stem bark aqueous extract of Schumanniophyton magnificum (ASMa) on the sexual maturation and fertility of the immature female Wistar rat. Forty immature female rats were randomized and divided into 4 groups of ten animals each and orally treated with the ASMa at doses of 0 (distilled water), 200 mg/kg, 400 mg/kg and 800 mg/kg /BW/day for 30 consecutive days. Body weight and food intake were recorded throughout the experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 26 publications
(21 reference statements)
1
11
2
Order By: Relevance
“…Here, uterine protein determination revealed that our extracts exhibit a positive effect on uterine proteins synthesis. Similarly, other researchers have demonstrated the positive effects of estrogenic substances in increasing proteins level (Bend et al, 2018;Lee and Lee, 1996).…”
Section: Discussionmentioning
confidence: 64%
“…Here, uterine protein determination revealed that our extracts exhibit a positive effect on uterine proteins synthesis. Similarly, other researchers have demonstrated the positive effects of estrogenic substances in increasing proteins level (Bend et al, 2018;Lee and Lee, 1996).…”
Section: Discussionmentioning
confidence: 64%
“…In Cameroon, Schumanniophyton magnificum has been recognized as a plant relieving infertile women. Subsequent studies have shown the accelerating and stimulating effect of Schumanniophyton magnificum on the growth and fertility of immature rats [6]. Recent phytochemical studies revealed the presence of secondary metabolites, such as flavonoids, alkaloids, polyphenols and steroids [7] [8].…”
Section: Introductionmentioning
confidence: 99%
“… 2007 ), and ability of the stem bark aqueous extract to improve fertility has also been demonstrated (Bend et al. 2018 ). S. magnificum is used as a snake bite remedy and as snake repellent in Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…Its stem bark is also used in Congo as an antiseptic for the treatment of gonorrhoea and ulcers. The stem bark extracts are also effective against Plasmodium falciparum (Bickii et al 2007), and ability of the stem bark aqueous extract to improve fertility has also been demonstrated (Bend et al 2018). S. magnificum is used as a snake bite remedy and as snake repellent in Nigeria.…”
Section: Introductionmentioning
confidence: 99%